2014
DOI: 10.3390/rs6020946
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Temperature Fields from MODIS Land Surface Temperature and Air Temperature Observations in a Sub-Arctic Alpine Environment

Abstract: Spatially continuous satellite infrared temperature measurements are essential for understanding the consequences and drivers of change, at local and regional scales, especially in northern and alpine environments dominated by a complex cryosphere where in situ observations are scarce. We describe two methods for producing daily temperature fields using MODIS -clear-sky‖ day-time Land Surface Temperatures (LST). The Interpolated Curve Mean Daily Surface Temperature (ICM) method, interpolates single daytime Ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 34 publications
1
54
0
2
Order By: Relevance
“…Although Li et al [14,17] used satellite observation to explore the effect of forest globally and found that forests decrease local temperatures in Europe, they focused on spatial patterns and did not consider the effects of background climate on forests during different yeas. Additionally, using two time observations to represent daily averages may also lead to some uncertainties [33]. Further studies should emphasize the effects of forests on the climate in Europe using both kinds of observations to explore the spatiotemporal patterns of forest effects and the effect of the background climate.…”
Section: Introductionmentioning
confidence: 99%
“…Although Li et al [14,17] used satellite observation to explore the effect of forest globally and found that forests decrease local temperatures in Europe, they focused on spatial patterns and did not consider the effects of background climate on forests during different yeas. Additionally, using two time observations to represent daily averages may also lead to some uncertainties [33]. Further studies should emphasize the effects of forests on the climate in Europe using both kinds of observations to explore the spatiotemporal patterns of forest effects and the effect of the background climate.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have successfully estimated high spatial resolution air temperature using satellite remote sensing [10][11][12][13][14][15][16]. Prihodko and Goward [8] used the temperature-vegetation index (TVX) from the Advanced Very High Resolution Radiometer (AVHRR) to estimate air temperature during the growing season of 1987 in Kansas, and found a strong correlation (r = 0.93) with a mean error of 2.92 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods for estimating T a from satellite optical-IR and passive microwave remote sensing have been widely implemented since the 1990s [1,2,[6][7][8][9][10][11][12][13]. Satellite remote sensing estimation methods for T a can be broadly classified as: (1) exploiting relationships between optical-infrared retrievals of land surface "skin" temperature (LST) and spectral vegetation indices such as the normalized difference vegetation index (NDVI) [1,11,14,15]; (2) exploiting relationships between LST and T a [16][17][18][19][20][21]; (3) the use of infrared soundings of atmospheric temperatures [22,23]; (4) the use of lower frequency (≤37 GHz) brightness temperatures (T b ) and surface emissivities from passive microwave radiometry [7,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%